Implementation of the Ottawa Ankle Rules by nurses working in an accident and emergency department. Issue 6 (November 1997) - Salt, P; Clancy, M
Abstract : OBJECTIVE: To assess whether accident and emergency (A&E) nurses using the Ottawa Ankle Rules could detect all ankle fractures. DESIGN: Prospective observational study. SETTING: A&E department of a university teaching hospital. SUBJECTS: All patients who presented with ankle injuries who were initially assessed by a nurse taught the Ottawa Ankle Rules. OUTCOME MEASURES: (1) The numbers of patients referred by the nurse for ankle radiography; (2) of these, the number with ankle fractures; (3) of those not sent for radiography initially by the nurse, the number who subsequently had x rays (ordered by the doctor) and had a fracture; (4) of those having no x rays, the number who reattended later. RESULTS: 324 patients were eligible; 238 had x rays at the request of the nurse (73%); 48 of these (20%) were diagnosed as having a fracture. Of those 86 patients not sent for radiography by the nurse, 19 subsequently had x ray examinations at the request of a doctor and no fracture was detected. Of the 67 not sent for radiography, none returned within the subsequent eight weeks. CONCLUSIONS: Nurses can apply the Ottawa Ankle Rules safely without missing acute fractures; that is, of those who were not sent for radiography by nurses, none subsequently reattended the A&E department or the trauma service of the Bristol Royal Infirmary during the following two months.